Synthetic Strategies toward the Indoxamycin Family - He, Chi; Zhu, Chenlong; Ding, Hanfeng (Synlett, 2014)
Indoxamycins A–F represent a novel class of polyketides isolated from saline cultures of actinomycetes. Owing to their stereochemically congested tricyclic structure and potent biological activities, indoxamycins are attractive targets for synthetic chemists. This report discusses recent progress toward the total synthesis of indoxamycins both by Carreira’s group and ours.
Keywords: polycycles; enynes; rearrangement; tandem reaction; total synthesis